Printing Spare Parts at Remote Locations: Fulfilling the Promise of Additive Manufacturing. Issue 6 (14th December 2020) - Westerweel, Bram; Basten, Rob; den Boer, Jelmar; van Houtum, Geert‐Jan
Abstract : We investigate the benefits of on‐site printing at remote geographic locations, where access to spare parts is intermittent and supplies are replenished at fixed intervals. Organizations typically have no solution to spare parts shortages other than expensive expediting orders, or waiting for a part to arrive with the next replenishment. We investigate whether on‐site three‐dimensional (3D) printing of spare parts can bring relief. Our work extends dual‐sourcing literature with fixed order cycles by considering two emergency supply options: expediting regular parts and 3D printing lower quality parts. We model the replenishment and emergency supply decisions as a Markov decision process and find that the optimal inventory control policy consists of two thresholds that control when to expedite, when to print and when to wait for regular parts via the next replenishment. We apply our model to a case study of the Royal Netherlands Army (RNLA) for her United Nations peacekeeping mission in Mali. Our results show that on‐site 3D printing, much more so than expediting, leads to large operational cost savings through on‐site inventory reductions and increased asset availability, thus increasing the ability of the RNLA to operate in remote locations. These results extend to many other organizations that operate in remote locations, for example, those in the mining and offshore industry.